2013
DOI: 10.4028/www.scientific.net/amr.671-674.774
|View full text |Cite
|
Sign up to set email alerts
|

Soft Rock Roadway Mesh Shell Lining Experimental Study of the Mechanical Properties

Abstract: Similar model experiment under confining pressure, research latticed shell lining the mechanical properties and the carrying capacity of new support for the underground engineering - network shell support, according to the model experiments and theoretical. Test results prove that the the latticed shell supporting structure has good mechanical properties and a high level of support is a reliable form of support. Can make up for the deficiencies of the existing soft rock roadway structure, calculated to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meng studied the mechanical properties and influencing factors of mudstone in coastal coal measures and proposed that the compressive strength and elastic modulus of mudstone decrease with the increase of water content [14]. Li et al experimented to study on the softening characteristics of mudstone in relation to moisture content [15] and showed that moisture content has a significant effect on shear properties reduction of mudstone and stress concentration is negatively correlated with moisture content. Wang investigated the pore structure and water imbibition behaviour through the mercury injection experiment [16] and proposed that the expansion deformation can be controlled by strengthening the lateral restraint.…”
Section: Introductionmentioning
confidence: 99%
“…Meng studied the mechanical properties and influencing factors of mudstone in coastal coal measures and proposed that the compressive strength and elastic modulus of mudstone decrease with the increase of water content [14]. Li et al experimented to study on the softening characteristics of mudstone in relation to moisture content [15] and showed that moisture content has a significant effect on shear properties reduction of mudstone and stress concentration is negatively correlated with moisture content. Wang investigated the pore structure and water imbibition behaviour through the mercury injection experiment [16] and proposed that the expansion deformation can be controlled by strengthening the lateral restraint.…”
Section: Introductionmentioning
confidence: 99%
“…At present, domestic and international scholars have conducted much scientific research and many industrial experiments on the mechanical properties [11][12][13], deformation, failure characteristics and mechanism [14,15], and theory and technology of soft rock roadways and surrounding rock control [16,17]. Little research has been performed on argillaceous weakly cemented rock [18,19], and even less work has been conducted to analyze the dynamic characteristics of such rock under dynamic loads.…”
Section: Introductionmentioning
confidence: 99%